Effects of Mediterranean diet and weight loss on blood-lipid profile in overweight adults with hypercholesterolemia - Innocenti, Augusto; Fusi, Jonathan; Cammisuli, Davide Maria; Franzoni, Ferdinando; Galetta, Fabio; Pruneti, Carlo (Progress in Nutrition, 2019)
Blood cholesterol has been positively associated with increased cardiovascular risk as a modifiable risk factors together with the lifestyle and diet. Furthermore, an improvement of the blood-lipid profile seems to be able to produce a decrease in cardiovascular events. Cholesterol plasma levels are related to the body mass index (BMI) and are affected by diet. The aim of this study was to evaluate the effectiveness of a Mediterranean diet (MD) weight-loss programme to improve blood cholesterol profiles in overweight adults subjected to real-world outpatient diet. Forty-nine hypercholesteraemic, overweight adults of both sexes were subjected to a dietary weight-loss intervention. Patients were prescribed a slightly hypocaloric MD for 16 weeks, followed by an 8-week follow-up period with a normocaloric diet. Data showed significant weight loss and cholesterol blood profile improvement both under the hypocaloric diet and during the follow-up period. In particular, the decrease in both Total and LDL-cholesterol was greater than their critical differences indicating the clinical relevance of blood lipid improvement induced by MD.